Creep behaviour of Nong Ngoo Hao subsoils at different deviator stress levels - Azlam, Mohamed Ali Mohamed; Balasubramaniam, A.S.; Tian Ho Seah; Noppadol Phien-Wej; Sugimoto, M.; German Academic Exchange Services (DAAD) (Bangkok : Asian Institute of Technology, 1996)
Three (3) test embankments 40m x 40m in dimensions have been constructed 15km east of Bangkok at the Nong Ngoo Hao site to understand the actual field deformation behaviour of the clay. The field instrumentation data shows continuous settlements with little dissipation of excess pore pressures have been taken place. Therefore, this research programme has been conducted in the laboratory to investigate the strain and the pore pressure dissipation with time. Thus this study, concentrates on the defmmation and creep characteristics both undrained and drained conditions at different deviator stress levels on Nong Ngoo Hao Clay. A total of eighteen (18) triaxial tests were pereformed in three (3) series, ( at 50, 70 and 90 percentage deviator stress levels) for weathered crust, very soft clay and soft clay. The samples were consolidated to insitu effective stresses under Ko conditions. They were then sheared at constant deviator stress in the compression mode. Test results of this study include the consolidation characteristics, the axial strain, the volumetric strain and the excess pore pressure behaviour of Nong Ngoo Hao Clay. The test results show that the creep strains for all stress levels are almost linear regardless of the drainage conditions. The axial strain observed under drained condition is higher than the undrained value. The results are in agreement with the data reported by HOLZER ( 1973 ) and ARULANANDAN ( 1971 ). The time dependent strain of Nong Ngoo Hao clay can be predicted by using SEMPLE's (1973) creep equation.
A thesis submitted m partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 1996
Keywords: Soils -- Creep -- Thailand -- Nong Ngoo Hao